KONSEKUENSI DARI KEBIJAKAN PEMERINTAH TENTANG VAKSINASI COVID-19 BAGI ANAK USIA 6-11 TAHUN TERHADAP PELAKSANAAN PEMBELAJARAN Di SD NEGERI 04 KAMPUNG OLO - Yolanda, Bella; Putra, Ikhsan Muharma; Wahyuni, Yanti Sri (Universitas Tanjungpura, 2022)
Government policies based on a circular from the Padang City Education and Culture Office regarding the implementation of vaccinations for children aged 6-11 years for the prevention of Covid-19 are known to have consequences for children, teachers and parents. at the age of 6-11 years towards learning at SD Negeri 04 Kampung Olo. The theory used in this research is the theory of structural functionalism of money proposed by Robert K. Merton. The research approach used is a qualitative approach with descriptive research type. Withdrawal of informants using purposive sampling technique with the number of informants 14 people. The types of data used in this research are primary data and secondary data. Data collection methods used are non-participant observation, in-depth interviews and document studies. Data analysis techniques used by the group with data analysis Miles and Huberman are data collection, data reduction, data presentation, and drawing conclusions. The results of this study show that the consequences of government policies regarding Covid-19 vaccination for children aged 6-11 years on the implementation of learning at SD Negeri 04 Kampung Olo have consequences, namely: 1) the consequences of policies on the implementation of learning, 2) Learning is divided into 2 shifts, 3) Differences in lesson hours, 4) grouping students online and offline.